Poéticas da visualidade: a literatura multigenérica na cena contemporânea brasileira - Pimentel, Daise de Souza (2014)
This work proposes a panoramic investigation on Brazilian Contemporary Literature. Its main focus is the mixture of the several codes and hybrid genres in this literature. The multiartist Nuno Ramos appears as the main writer who represents this tendency. His works Cujo (1993), O pão do corvo (2001), Ensaio Geral (2007), Ó (2008), and Junco (2011) are analysed briefly in this dissertation. In a complementary way, my text also brings to light some brief analyses on short stories by Silviano Santiago, Sérgio Sant’Anna and João Gilberto Noll and on a novel by Lourenço Mutarelli, a graphic-novel writer. To give theorical support to my own arguments, I had the help of texts by Walter Benjamin, Maurice Merleau-Ponty, Michel Foucault, Jacques Rancière, David Harvey, Hal Foster, Georges DidiHuberman, Catherine Millet, Anne Cauquelin, Lucia Helena, Helena Bonito Pereira, Karl Erik Schøllhammer, Eduardo Jorge and others literary philosophers, historians and critics of the current art.